Potassium in the syndrome of inappropriate antidiuretic hormone secretion. Issue 648 (October 1979) - Padfield, P. L.; Morton, J. J.
Abstract : Serum potassium concentration was normal (greater than or equal to 3.6 mmol/l) in 29 of 32 patients with the syndrome of inappropriate antidiuretic hormone excess (SIADH) associated with a bronchogenic carcinoma. In 11 of the patients there was no significant change in serum potassium concentration after correction of the syndrome, by fluid restriction. Hypokalaemia is thus an uncommon finding in SIADH due to bronchogenic carcinomas.